High dielectric tunability of Ba(Zr0.2Ti0.8)O3–(Ba0.7Ca0.3)TiO3 thick films modified by a solution-immersion process. (April 2016) - Feng, Zuyong; Wu, Nan; Zhang, Wei; Luo, Jie; Tang, Xingui; Cheng, Zhenxiang; Shi, Dongqi; Dou, Shixue
Graphical abstract: Highlights: A solution-immersion process is used for the fabrication of dense films. High-quality Ba(Zr0.2 Ti0.8 )O3 –(Ba0.7 Ca0.3 )TiO3 thick films were synthesized. Excellent dielectric properties were obtained. High dielectric tunability of 76.7% was achieved. Abstract: High-quality lead-free 0.5Ba(Zr0.2 Ti0.8 )O3 –0.5(Ba0.7 Ca0.3 )TiO3 thick films with the thickness of 8 μm were prepared by screen printing with a solution-immersion process. The solution-modified films near the morphotropic phase boundary (MPB) showed very dense and homogenous microstructure with large grain size, and exhibited moderate dielectric constant of 1680 and low dielectric loss of 1.38% at 10 kHz with 0 V bias at room temperature. High dielectric tunability up to 76.7% at 12 kV/mm and 10 kHz was achieved in the modified films. The excellent dielectric properties associated with good microstructure and MPB composition, make the lead-free films be a promising candidate for dielectric tunable capacitor applications.